PENGARUH ETIKA KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI KEMENTERIAN PARIWISATA - Agustina Massora (Jurnal Manajemen FE-UB, 2019)
This study aims to determine the extent of ethical relations, organizational commitment toemployee performance in the Ministry of Tourism, and to find out how the influence of ethicalfactors, organizational commitment to employee performance. In this study the authorsdistributed questionnaires to 86 respondents with simple random sampling technique and the dataanalysis method used was multiple regression and multiple correlation F test.Based on the calculation, a regression of Y = 0.686 + 0.767 X1 + 0.069 X2 means that anyincrease in ethical variables (X1) will be followed by an increase in employee performance, eachincrease in organizational commitment will be followed by an increase in employee performance.With R = 0.90, this shows that there is a level of strong and positive relationship between ethicsand organizational commitment with employee performance. This means that an increase inethics and organizational commitment leads to an increase in employee performance. Fromtesting with the F hypothesis it is known that the F count is 177.070 while the F table is 3.11 withthe numerator dk 2 (= k-1 = 3-1) and the denominator n - k = 86 - 3 = 83. Because the F count isgreater instead of F table, Ho is rejected and Ha is accepted, meaning that there is a relationshipbetween ethics (X1) and organizational commitment (X2) on employee performance (Y).From the coefficient of determination of 81%, this shows that the influence of ethics andorganizational commitment by 81% on the increase in employee performance, while theremaining 19% is influenced by other variables not included in this research model. For furtherresearch is expected to add other variables related to employee performance such as training,motivation, job satisfaction and so on, so it can be better known the influence of other factors thatwill affect employee performance.